Structure and emplacement of the Nandurbar-Dhule mafic dyke swarm, Deccan Traps, and the tectonomagmatic evolution of flood basalts - RAY, R; SHETH, HC; MALLIK, J (Bulletin of Volcanology, 2007)
Flood basalts, such as the Deccan Traps of India, represent huge, typically fissure-fed volcanic provinces. We discuss the structural attributes and emplacement mechanics of a large, linear, tholeiitic dyke swarm exposed in the Nandurbar-Dhule area of the Deccan province. The swarm contains 210 dykes of dolerite and basalt > 1 km in length, exposed over an area of 14,500 km(2). The dykes intrude an exclusively basaltic lava pile, largely composed of highly weathered and zeolitized compound pahoehoe flows. The dykes range in length from < 1 km to 79 km, and in thickness from 3 to 62 m. Almost all dykes are vertical, with the others nearly so. They show a strong preferred orientation, with a mean strike of N88 degrees. Because they are not emplaced along faults or fractures, they indicate the regional minimum horizontal compressive stress (sigma (3)) to have been aligned similar to N-S during swarm emplacement. The dykes have a negative power law length distribution but an irregular thickness distribution; the latter is uncommon among the other dyke swarms described worldwide. Dyke length is not correlated with dyke width. Using the aspect ratios (length/thickness) of several dykes, we calculate magmatic overpressures required for dyke emplacement, and depths to source magma chambers that are consistent with results of previous petrological and gravity modelling. The anomalously high source depths calculated for a few dykes may be an artifact of underestimated aspect ratios due to incomplete along-strike exposure. However, thermal erosion is a mechanism that can also explain this. Whereas several of the Nandurbar-Dhule dykes may be vertically injected dykes from shallow magma chambers, others, particularly the long ones, must have been formed by lateral injection from such chambers. The larger dykes could well have fed substantial (> 1,000 km(3)) and quickly emplaced (a few years) flood basalt lava flows. This work highlights some interesting and significant similarities, and contrasts, between the Nandurbar-Dhule dyke swarm and regional tholeiitic dyke swarms in Iceland, Sudan, and elsewhere.